HIV-Associated Neurocognitive Disorders: The First Longitudinal Follow-Up of a cART-Treated Cohort of Older People in Sub-Saharan Africa. (1st June 2022) - Spooner, Rebecca; Ranasinghe, Sherika; Urasa, Sarah; Yoseph, Marcella; Koipapi, Sengua; Mukaetova-Ladinska, Elizabeta B.; Lewis, Thomas; Howlett, William; Dekker, Marieke; Kisoli, Aloyce; Gray, William K.; Walker, Richard W.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: HIV-associated neurocognitive disorders (HAND) are a highly prevalent chronic complication in older people living with HIV (PLWH) in high-income countries. Although sub-Saharan Africa has a newly emergent population of older combination antiretroviral therapy (cART)-treated PLWH, HAND have not been studied longitudinally. We assessed longitudinal prevalence of HAND and have identified possible modifiable factors in a population of PLWH aged 50 years or older, over 3 years of follow-up. Methods: Detailed neuropsychological and clinical assessment was completed annually in the period 2016–2019 in a systematic sample of cART-treated PLWH in Kilimanjaro, Tanzania. A consensus panel defined HAND using American Academy of Neurology criteria for asymptomatic neurocognitive impairment, mild neurocognitive disorder, and HIV-associated dementia. HIV disease severity and other factors associated with HAND progression, improvement, and stability were evaluated in individuals fully assessed at baseline and in 2019. Results: At baseline, 47% of the cohort (n = 253, 72.3% female individuals) met HAND criteria despite good HIV disease control [Y1 59.5% (n = 185), Y2 61.7% (n = 162), and Y3 57.9% (n = 121)]. Of participants fully assessed at baseline and year 3 (n = 121), HAND remained stable in 54% (n = 57), improved in 15% (n = 16), and declined in 31% (n = 33). Older age and lower education level significantly predicted HAND progression, whereas HIV-specific factors did not. Male sex and shorter cART duration were associated with improvement. Conclusions: In this first longitudinal study characterizing clinical course of HAND in older cART-treated PLWH in sub-Saharan Africa, HAND was highly prevalent with variable progression and reversibility. Progression may be more related to cognitive reserve than HIV disease in cART-treated PLWH.